"OUT OF POCKET PAYMENT" FOR HEALTHCARE : AGE AND GENDER DIFFERENCES - Vojvodic, Katarina; Terzic Supis, Zorica (Medicinski podmladak, 2023)
Out-of-pocket payments for health care as one of the ways of health care financing is present in many countries and can lead to a financial burden of healthcare on the household level. This could lead to restrictions on other necessary goods and lower the expected standard of living. The frequency of out-of-pocket payments is often associated with gender and age. Biological and socio-economic differences between the genders and differences that arise in the aging process can influence the more frequent occurrence of financial burdens due to out-of-pocket payments. There is a difference between men and women in the occurrence of malignant diseases (specific to sex), differences in the use of health care, the prevalence of chronic diseases, self-assessment of health, poverty, financial independence, and the type of household. All mentioned can lead to a different frequency of out-of-pocket payments and the financial burden of health care. Keywords: out – of - pocket payments, financial burden, healthcare, women, men, 65 and more years old